Hate Speech in Gus Miftah Instagram Comment Section: An Ice Tea Seller Case Study - Sirait, Naomi; Purba, Raysa; Silitonga, Mega Uli Arta; Putri, Dian Marisha (TALENTA, 2025)
The purposes of this research are to find the hate speech found in Islamic preacher Gus Miftah’s Instagram account during the iced tea seller controversy. This study employed a descriptive qualitative approach. The data was collected manually from Instagram comments related to a viral incident involving Gus Miftah, ensuring the selection of comments that exhibited clear hostility or aggression. Using the theory for classifying hate speech developed by (Mondal et al., 2017) and the impoliteness strategies developed by (Culpeper’s, 2015), this study distinguishes six categories of hate speech: religion (41.9%), behavior (27.5%), physical (25.06%), class (4.35%), disability (1.08%), and gender (0.2%). Furthermore, bald-on-record impoliteness was the most often used strategy (45.14%), indicating users’ direct animosity. The study offers a detailed understanding of the rhetorical and ideological foundations of hate speech and contributes new insights to hate speech studies by placing the analysis within the cultural and religious context of Indonesia.